2016
DOI: 10.22502/jlmc.v4i1.75
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Pediatric Dermatoses

Abstract: Introduction: Skin diseases are common in children; however they differ depending in age, region, socioeconomic status and climate. Many studies have been done to study pattern of dermatological disease in pediatric age group but only few studies have been done in its seasonal variation. So we decided to study seasonal variation of pediatric dermatoses.   Methods: This was retrospective study done from hospital record of Lumbini Medical College Teaching Hospital (LMCTH). All children 14 years and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
1
5
1
Order By: Relevance
“…e hot and humid condition during summer season might be the reason for the increase in bacterial infections and miliaria. e overall prevalence of scabies (7.53%) in our study was slightly greater than that of Poudyal et al [10], but lower than that of Banerjee et al [16] in India and Shrestha and Mikrani [9] in Nepal. Studies from Turkey had a very low incidence of scabies as compared to the subcontinent [14,18].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…e hot and humid condition during summer season might be the reason for the increase in bacterial infections and miliaria. e overall prevalence of scabies (7.53%) in our study was slightly greater than that of Poudyal et al [10], but lower than that of Banerjee et al [16] in India and Shrestha and Mikrani [9] in Nepal. Studies from Turkey had a very low incidence of scabies as compared to the subcontinent [14,18].…”
Section: Discussioncontrasting
confidence: 73%
“…However, the most common dermatosis in our study was infectious dermatoses followed by eczema. Other studies from Nepal have shown that infections and eczema were also the two most common conditions [ 3 , 4 , 8 , 9 ]. Similar results were also noted from several studies from India [ 2 , 10 – 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[17][18][19][20] Infections and infestations were most common dermatoses similar to other studies from Nepal and other developing countries. 2,5,[10][11][12][13][14][15]17,18,[21][22][23]…”
Section: Association Of Personal Hygiene With Infectious Dermatosesmentioning
confidence: 99%
“…In infants, number of non-infectious dermatoses was higher than infectious dermatoses and infectious dermatoses were common in older children and adolescents similar to other studies. 1,18,[22][23][24] F I G U R E 1 Age and gender distribution of participants.…”
Section: Association With Sociodemographic Factorsmentioning
confidence: 99%